Clinical profile of patients with hypertensive emergencies in a tertiary care hospital - Murty, S. Narasimha; Rao, S. S. V. V. Narsinga; Veeramani Kartheek, A. S. (International Journal of Research in Medical Sciences, 2023)
Background: Hypertensive emergency is defined by systolic blood pressure (SBP) ≥180 mmHg and/or diastolic blood pressure (DBP) ≥120 mmHg with acute target organ damage. Hypertensive emergencies can be life threatening and fatal unless timely treated. In the present study we aim to study the clinical profile and outcome of patients admitted with hypertensive emergency in the medical intensive care unit in our hospital. Methods: A cross-sectional observational study of all cases with hypertensive emergency admitted in Medical Intensive care unit (ICU) in Government General Hospital, Srikakulam during the study period was conducted. The clinical profile and outcome of the patients were assessed. Results: Out of the fifty patients in the present study, about 36 (72%) were males and 14 were females (28%) and about one third of the patients (36%) belonged to the age group of 60-69 years. Diabetes mellitus (30%) and dyslipidemia (40%) were the commonly encountered comorbidities in the study population. Most frequent presenting symptoms were neurological deficits (50%) followed by dyspnoea (32%) and chest pain (24%). Intracerebral haemorrhage was the commonest target organ damage found in 30% of the patients. Patients presenting with hypertensive emergencies with neurological target organ damage had statistically significant increased chance of mortality (p=0.007). Conclusions: As hypertension emergencies are consequence of uncontrolled hypertension, it is important to educate and bring awareness among public regarding the screening, early detection, and adherence to prescribed medication for hypertension to avoid adverse clinical outcomes.